"That Democratic Ink Must Be Wiped Away": Hobbes and the Normativity of Democracy. Issue 3 (2021) - Holman, Christopher
Abstract: Hobbes's preference for monarchical sovereign forms and his critique of democratic political organization are well known. In this article I suggest, however, that his opposition to democratic life constitutes the central frame through which we must understand some of the most important theoretical mutations that occur throughout the various stages of his civil science. Key alterations in the Hobbesian political theory from The Elements of Law to Leviathan can be interpreted as efforts to retroactively foreclose the emergence of a substantive democratic normativity that the prior theoretical framework allowed for or suggested. Hobbes's opposition to democracy is ultimately so significant so as to fundamentally structure various key elements of his political philosophy.